1989
DOI: 10.1093/ajcn/50.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic activity in sera from obese children before and after weight reduction

Abstract: The adipogenic and mitogenic potentials of sera obtained from obese children before and after weight reduction and from lean control subjects were studied in clonal 3T3 L1 fibroblasts. The sera from the lean (n = 14) and obese (n = 12) children under habitual diet contained similar adipogenic activity. However, when the obese children underwent a weight-reduction program for 3 wk (600 kcal/d), the potential of their sera to stimulate glycero-phosphate dehydrogenase, an index of adipogenic activity, was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Indeed, infants fed formula had far greater postprandial levels of insulin on day 6 of life than infants fed cow's milk-based formula [43]. High insulin and IGF-1 values can enhance both growth during the first 2 years of life [44,45] as well as adipogenic activity and adipocyte differentiation [46] (fig. 4).…”
Section: Potential Causes For the Protective Effects Of Breastfeedingmentioning
confidence: 99%
“…Indeed, infants fed formula had far greater postprandial levels of insulin on day 6 of life than infants fed cow's milk-based formula [43]. High insulin and IGF-1 values can enhance both growth during the first 2 years of life [44,45] as well as adipogenic activity and adipocyte differentiation [46] (fig. 4).…”
Section: Potential Causes For the Protective Effects Of Breastfeedingmentioning
confidence: 99%
“…According this “early protein hypothesis,” higher protein intakes during formula and complementary feeding, when intake is two to four times higher than requirements, program more rapid growth and later obesity by enhancing insulin and insulin‐like growth factor I (IGF‐1) secretion. These higher levels would, in turn, enhance growth (Hoppe et al,2004) by up‐regulating adipogenesis and adipocyte differentiation (Hauner et al,1989).…”
Section: Introductionmentioning
confidence: 99%
“…Koletzko and colleagues demonstrated that infants given formula with high protein content compared to infants given formula with low protein content resulted in increased weight at 2 years of age with no effect on infant length [53]. It is thought that the higher protein consumption results in higher insulin secretion and stimulates the expression of insulin-like growth factor I (IGF-I), leading to more adipogenic activity and adipocyte differentiation [54, 55]. Additionally, behavioural differences between breast-fed and formula-fed infants may affect infant energy intake.…”
Section: Discussionmentioning
confidence: 99%